PGRS Domain of Rv0297 of Mycobacterium tuberculosis Is Involved in Modulation of Macrophage Functions to Favor Bacterial Persistence - Sharma, Tarina; Grover, Sonam; Arora, Naresh; P, Manjunath; Ehtesham, Nasreen Zafar; Hasnain, Seyed Ehtesham (Frontiers in Cellular and Infection Microbiology, 2020)
Mycobacterium tuberculosis (M. tb) Rv0297-encoded PE_PGRS5 has been known to be expressed at the later stages of infection and in acidified phagosomes during transcriptome and proteomic studies. The possible role of Rv0297 in the modulation of phagosomal maturation and in providing protection against a microbicidal environment has been hypothesized. We show that Rv0297PGRS is involved in modulating the calcium homeostasis of macrophages followed by impedance of the phagolysosomal acidification process. This is evident from the downregulation of the late endosomal markers (Rab7 and cathepsin D) in the macrophages infected with recombinant Mycobacterium smegmatis (rM.smeg)—M.smeg_Rv0297 and M.smeg_Rv0297PGRS—or treated with recombinant Rv0297PGRS protein. Macrophages infected with rM.smeg expressing Rv0297 produce nitric oxide and undergo apoptosis, which may aid in the dissemination of pathogen in the later stages of infection. Rv0297 was also found to be involved in rescuing the bacterium from oxidative and hypoxic stress employed by macrophages and augmented the survivability of the recombinant bacterium. These results attribute to the functional significance of this protein in M.tb virulence mechanism. The fact that this protein gets expressed at the later stages of lung granulomas during M.tb infection suggests that the bacterium possibly employs Rv0297 as its dissemination and survival strategy.